Multiple Patients With Burn Injury Induced by a Chemical Explosion Managed by Physician-Staffed Helicopters. (3rd January 2019) - Kondo, Akihiko; Jitsuiki, Kei; Osaka, Hiromichi; Takeuchi, Ikuto; Ishikawa, Kouhei; Omori, Kazuhiko; Yanagawa, Youichi
ABSTRACT: On December 1, 2017, the Fuji factory of Arakawa Chemical Industries exploded. Dust that formed as a byproduct from the crushing and packing process of the resin for ink exploded at the facility. The Fuji City Fire Department requested the dispatch of 2 physician-staffed helicopters (known as a doctor helicopter [DH] in Japan). The first party of emergency services established a headquarters and first-aid station. However, this area was feared to be at risk of a second explosion. Physicians performed re-triage for all 11 burned patients. Three severely injured patients were transported to emergency medical service centers either by ground ambulance or the DH without undergoing any decontamination. The physician who escorted the patient by ground ambulance complained of a headache. One of the severely injured patients was treated at a local hospital and then transported to an emergency medical service center after undergoing decontamination and intubation. Fortunately, all patients who were transported to medical facilities obtained a survival outcome. Chemical, biological, radiological, nuclear, and explosive incidents are rare but can be fatal for responders to these types of disaster. Therefore, all who work in these settings should be prepared and trained adequately to ensure that they have the knowledge and skill to both manage patients and protect themselves from harm. ( Disaster Med Public Health Preparedness. 2019;13:799–805)